Thermal-fluid field coupling simulation and characteristic analysis on internal temperature of oil-immersed transformers - SHAO Xianjun; GAO Yiran; JIN Lingfeng; ZHAN Jiangyang; ZHENG Yiming; LI Yuan (Zhejiang dianli, 2023)
The temperature rise at winding hotspots is a critical metric for assessing the operational condition and remaining lifespan of oil-immersed transformers. In the context of a 110 kV oil-immersed self-cooling transformer， a comprehensive two-dimensional closed-loop full-scale thermal-fluid simulation model incorporating the equivalent geometric structures of radiators is constructed. The model predicts temperatures with an error of less than 5 ℃ when compared to temperature rise test results， demonstrating a high level of accuracy. Simulation results bring to light the presence of an oil stagnant zone within the horizontal oil duct of the windings. To optimize oil circulation in this area， the impact of horizontal oil duct width and the number of baffle plates on oil flow rate and winding temperature rise is analyzed. The study findings suggest that widening the horizontal oil duct reduces both the average winding temperature and hotspot temperature. Additionally， the installation of baffle plates significantly improves oil flow rate in the horizontal oil duct， consequently reducing the average winding temperature rise. Under the specified conditions， the installation of five baffle plates emerges as the optimal solution for achieving comprehensive heat dissipation performance.